Pengaruh Profitabilitas, Ukuran Perusahaan, Dan Komite Audit Terhadap Audit Delay : Studi Pada Perusahaan Sub Sektor Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Ayi Mohamad Sudrajat; Bella Siti Nurhasanah (Universitas 45 Surabaya, 2023)
This research aims to determine the effect of profitability, company size and audit committee on audit delay with the research subject being property and real estate sub-sector companies listed on the Indonesian Securities Exchange with the unit of analysis being annual financial reports for the 2020-2022 period. The research method uses descriptive and associative methods. The sample in this research was 46 companies in the property and real estate sub-sector. The sampling technique was carried out by random sampling. The analytical method used is panel data regression analysis using STATA 14 software. The research results show that partially profitability has a significant negative effect on audit delay, partially company size has an insignificant negative effect on audit delay, partially the audit committee has an insignificant positive effect on audit delay. As for the simultaneous results of profitability, company size and audit committee have a significant influence on audit delay with a coefficient of determination in the form of an overall value of 0.0821 or 8.21% and the remaining 91.79% is influenced by other variables outside this research.